2012
DOI: 10.3892/mmr.2012.995
|View full text |Cite
|
Sign up to set email alerts
|

The A to G polymorphism at -1082 of the interleukin-10 gene is rare in the Han Chinese population

Abstract: Interleukin-10 (IL-10) is a multifunctional anti-inflammatory cytokine involved in various physiological and pathophysiological processes including cardiovascular disease. It has been reported that 50-75% of the variation in IL-10 production is genetically controlled. In the present study, the IL-10 -1082A/G (rs1800896) polymorphism was detected in 174 coronary artery disease (CAD) patients confirmed by selective coronary angiography and 176 age and gender-matched controls from the Jiangsu area (East China). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…However, some studies reported inconsistent results. Guo et al (2012) observed that IL-10 -1082A/ G was unlikely to be a significant biomarker to CAD susceptibility in the Han Chinese population. Koch et al (2001) carried out a study in a German 998 patients with CAD and 340 control subjects, and did not reported an correlation of IL-10 -1082A/G and -592A/C polymorphisms with the risk of CAD.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, some studies reported inconsistent results. Guo et al (2012) observed that IL-10 -1082A/ G was unlikely to be a significant biomarker to CAD susceptibility in the Han Chinese population. Koch et al (2001) carried out a study in a German 998 patients with CAD and 340 control subjects, and did not reported an correlation of IL-10 -1082A/G and -592A/C polymorphisms with the risk of CAD.…”
Section: Discussionmentioning
confidence: 90%
“…IL-10 is a member of the immunoregulatory cytokine family, and is located on chromosome 1q31-1q32. Many published studies have indicated that polymorphisms in the IL-10 gene are correlated with pathogenesis of CAD in different populations; however, the results remain conflicting (Blagodatskikh et al, 2010;Koch et al, 2001;Guo et al, 2012;Liu et al, 2013;Elsaid et al, 2014;Ren and She, 2015).Here, we carried out a study to assess the role of two common polymorphic sites in IL-10 gene (-1082A/ G and -592A/C) in the CAD risk.…”
Section: Introductionmentioning
confidence: 95%
“…Li et al (2015) conducted a case-control study in the Chinese population and did not find any association between IL-10-1082A/G polymorphism and the risk of coronary artery diseases. Similarly, Guo et al (2012) reported that IL-10-1082A/G polymorphism is unlikely to be associated with CAD. In contrast, a study by Ren and She (2015) with 325 CAD patients and 342 controls reported that IL-10-1082A/G polymorphism contributes to the risk for CAD, especially in individuals with hypertension or diabetes mellitus, as well as in smokers.…”
Section: Discussionmentioning
confidence: 96%
“…Several previous studies reported an association between IL-10-1082A/G polymorphism and the development of coronary artery diseases; however, the results were inconclusive (Guo et al, 2012;Elsaid et al, 2014;Li et al, 2015;Ren and She, 2015). Li et al (2015) conducted a case-control study in the Chinese population and did not find any association between IL-10-1082A/G polymorphism and the risk of coronary artery diseases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation